2022
DOI: 10.2337/db21-0934
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin Prevents Hyperglycemia-Associated Muscle Extracellular Matrix Accumulation and Improves the Adaptive Response to Aerobic Exercise

Abstract: Chronic hyperglycemia is associated with low response to aerobic exercise training in rodent models and humans, including reduced aerobic exercise capacity and impaired oxidative remodeling in skeletal muscle. Here, we investigated whether glucose lowering with the sodium glucose cotransporter-2 inhibitor (SGLT2i), canagliflozin (Cana; 30 mg/kg/day), could restore exercise training response in a model of hyperglycemia (low dose streptozotocin; STZ). Cana effectively prevented increased blood glucose in STZ-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…It has been suggested that SGLT2 inhibition could ameliorate the remodeling of skeletal muscle. In a mouse model with reduced aerobic exercise capacity due to chronic hyperglycemia, treatment with canagliflozin led to an increase in the proportion of oxidative fibers, suggesting that impaired muscle remodeling was prevented by treatment with SGLT2 inhibitors [ 169 ]. In a high-fat diet mouse model in which mice were treated with canagliflozin for 8 weeks, SGLT2 inhibition induced a reduction in inflammatory cytokine levels and macrophage accumulation [ 170 ].…”
Section: Sglt2-inhibition-mediated Effects On the Underlying Pathophy...mentioning
confidence: 99%
See 3 more Smart Citations
“…It has been suggested that SGLT2 inhibition could ameliorate the remodeling of skeletal muscle. In a mouse model with reduced aerobic exercise capacity due to chronic hyperglycemia, treatment with canagliflozin led to an increase in the proportion of oxidative fibers, suggesting that impaired muscle remodeling was prevented by treatment with SGLT2 inhibitors [ 169 ]. In a high-fat diet mouse model in which mice were treated with canagliflozin for 8 weeks, SGLT2 inhibition induced a reduction in inflammatory cytokine levels and macrophage accumulation [ 170 ].…”
Section: Sglt2-inhibition-mediated Effects On the Underlying Pathophy...mentioning
confidence: 99%
“…Decreasing oxidative stress or inflammation could have a beneficial effect in preventing a shift in muscle fiber type in skeletal muscle [ 170 ]. Furthermore, treatment with canagliflozin was found to restore exercise-induced angiogenesis in mice that were exposed to hyperglycemia [ 169 ]. The question of whether SGLT2 inhibitors could have similar effects on amelioration of the HF-induced remodeling in skeletal muscle has not yet been studied.…”
Section: Sglt2-inhibition-mediated Effects On the Underlying Pathophy...mentioning
confidence: 99%
See 2 more Smart Citations
“…These observations suggest that the metabolic effect of SGLT2 inhibitors on skeletal muscle depends on glucose availability. Several studies have reported that SGLT2 inhibitors can improve the endurance capacity of streptozotocin (STZ)‐induced hyperglycaemic mice 12,13 . However, there is no detailed analysis of how SGLT2 inhibitors affect skeletal muscle metabolism in obese diabetic mice focusing on the differential responses of oxidative and glycolytic muscles.…”
Section: Introductionmentioning
confidence: 99%